2011
DOI: 10.1590/s0100-879x2011000700015
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and biochemical parameters of patients with metabolic syndrome and the participation of oxidative and nitroactive stress

Abstract: Metabolic syndrome (MS) is a multifactorial disease involving inflammatory activity and endothelial dysfunction. The aim of the present study was to evaluate the relationship between the changes in lipoperoxidation, in immunological and biochemical parameters and nitric oxide metabolite (NOx) levels in MS patients. Fifty patients with MS (4 males/46 females) and 50 controls (3 males/47 females) were studied. Compared to control (Mann-Whitney test), MS patients presented higher serum levels (P < 0.05) of fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Simão et al, in a case-control study, identified lower concentrations of nitrite/nitrate in the MetS group, reflecting lower concentrations of • NO [50]. In opposition to these observations, Ueyama et al [51] showed that the concentrations of nitrite/nitrate increased when the number of the MetS diagnostic criteria was progressively augmented in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Simão et al, in a case-control study, identified lower concentrations of nitrite/nitrate in the MetS group, reflecting lower concentrations of • NO [50]. In opposition to these observations, Ueyama et al [51] showed that the concentrations of nitrite/nitrate increased when the number of the MetS diagnostic criteria was progressively augmented in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although endothelial dysfunction has been considered an important issue in patients with the MetS, results of studies on serum NOx levels in these patients have been contradictory ( 56 – 58 ) . The majority of the studies support the hypothesis that even in low-grade inflammatory processes, such as in the MetS, NO is consumed in a reaction with superoxide anion yielding a strong oxidant species, ONOO − , which in turn accelerates the lipid peroxidation reaction ( 59 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Inducible NOS www.nature.com/aps Pârvu AE et al Acta Pharmacologica Sinica npg (NOS2/iNOS) is expressed by various cells, such as macrophages and fibroblasts, in response to inflammatory stimuli, and it produces large amounts of NO. Since large amounts of NO are toxic, NO has been implicated in the pathophysiology of several inflammatory conditions [9][10][11][12] . In such diseases, under conditions of high and sustained NO production, reactive nitrogen oxide species (RNS) (such as nitrogen dioxide, NO 2 ; dinitrogen trioxide, N 2 O 3 ; and peroxynitrite, ONOO -) are formed by reactions with reactive oxygen species (ROS), and may result in nitrosative or oxidative stress [13,14] .…”
Section: Introductionmentioning
confidence: 99%